Storage stability of electrospun pure gelatin stabilized with EDC/Sulfo‐NHS. Issue 9 (6th September 2018) - Ghassemi, Zahra; Slaughter, Gymama
Abstract: With the rapid development of biomimetic polymers for cell‐based assays and tissue engineering, crosslinking electrospun nanofibrous biopolymer constructs is of great importance for achieving sustainable and efficient three‐dimensional scaffold constructs. Uncrosslinked electrospun gelatin nanofibrous constructs immediately and completely dissolved in aqueous solutions due to their aqueous solubility and poor storage stability. Here, a novel and versatile approach for the fabrication and crosslinking of electrospun gelatin construct with tunable porosity and high aspect ratio nanofibers is presented. Uncrosslinked electrospun gelatin/genipin nanofibrous and pure gelatin nanofibrous constructs exhibited smooth surfaces that were well‐defined, with a diameter in the range of 448 ± 364 nm and 257 ± 57 nm, respectively. Dehydrothermal, genipin‐EDC/Sulfo‐NHS, and EDC/Sulfo‐NHS crosslinking approaches were examined to achieve insoluble gelatin nanofibrous constructs that were suitable for cell‐based assays. Mechanical characterization demonstrated that the pure gelatin nanofibrous construct crosslinked via EDC/Sulfo‐NHS exhibited an increased mechanical strength and stiffness and showed no dissolution in aqueous solutions and retained its fiber morphology. An excellent 1 month storage stability was demonstrated at 22, 4, −20, and −80°C (dehydrated) and at 4°C (hydrated). The as‐crosslinked gelatin nanofibrous construct was highly biocompatible (90% cell viability), as demonstrated by the promoted proliferation of PC12 cells. Abstract :